Effects of rape/common vetch intercropping on biomass, soil characteristics, and microbial community diversity - Qu, Jiahui; Li, Lijun; Wang, Ying; Yang, Jinhu; Zhao, Xinyao (Frontiers in environmental science, 2022)
Legume–brassica intercropping is widely used to increase productivity in modern, sustainable agricultural systems. However, few studies have assessed the linkages between soil properties and soil microorganisms. Soil microorganisms play a key role in soil nutrient turnover and plant community composition. To elucidate the responses of soil microbial community diversity and structure to intercropping, we conducted a 2-year experiment based on common vetch (CV) monoculture, rape (R) monoculture, and common vetch–rape intercropping (IRCV) with phosphorus (P) addition in alkaline soil. The microbial communities of bacteria and fungi in the rhizosphere soil were examined based on high-throughput sequencing targeting the 16S rRNA and ITS genes, respectively. In addition, we analyzed changes in soil properties and enzyme activities. Intercropping significantly increased dry matter (up to 98.86% and 81.48%, respectively dry matter is the aboveground biomass.) compared with common vetch monoculture. Intercropping decreased soil bulk density and pH and enhanced soil available phosphorus (AP) by 14.54–34.38%, 7.25–22.67%, soil organic matter (SOM) by 15.57–22.85, 6.82–15.57%, soil sucrase (Suc.) by 13.69–16.10%, 35.57–40.24% compared to monoculture common vetch and rape, respectively. However, bacterial alpha diversity was higher under rape monoculture than IRCV. In addition, the dominant soil bacterial phyla Proteobacteria (1.25–3.60%), Gemmatimonadetes (7.88–15.16%), Bacteroidetes (9.39–11.76%), and Rokubacteria (0.49–5.69%) were present at greater abundance with IRCV relative to those with CV and R, but phyla Chloroflexi was significantly decreased by 11.56–12.94% with IRCV compared with the other two treatments. The redundant analysis showed that SOM and AP were positively correlated with the dominant bacterial and fungal flora. Common vetch–rape intercropping resulted in increased biomass and altered soil microbial community composition as well as soil properties. Our results showed that intercropping systems positively improve soil microbial activity; this strategy could help in the cultivation of multiple crops and improve soil properties through sustainable production.